Environmental Macrolide–Lincosamide–Streptogramin and Tetracycline Resistant Bacteria - Roberts, Marilyn C. (Frontiers in Microbiology, 2011)
Bacteria can become resistant to antibiotics by mutation, transformation and/or acquisition of new genes which are normally associated with mobile elements (plasmids, transposons, and integrons). Mobile elements are the main driving force in horizontal gene transfer between strains, species and genera and are responsible for the rapid spread of particular elements throughout a bacterial community and between ecosystems. Today, antibiotic resistant bacteria are widely distributed throughout the world and have even been isolated from environments that are relatively untouched by human civilization. In this review macrolides, lincosamides, streptogramins, and tetracycline resistance genes and bacteria will be discussed with an emphasis on the resistance genes which are unique to environmental bacteria which are defined for this review as species and genera that are primarily found outside of humans and animals.